Qualitative Study of the Implementation of Occupational Health and Safety Culture on Employee Performance PT Bahana Prima Nusantara - Jesica Chriscalty Kasi; Febrianti Dharma Birana; Andi Alim (The Indonesian Journal of Occupational Safety and Health)
Introduction: This study aims to examine the impact of implementing the Occupational Safety and Health (OSH) culture on employee performance, focusing on knowledge, workload, and work environment aspects at PT Bahana Prima Nusantara. Method: This study uses a qualitative method that seeks to examine the implementation of OSH culture to employee performance. This research was conducted in natural situations so that there were no limitations in understanding the research being studied. The number of informants is 5 people. Data collection is done through interviews, observation, and documentation. Result: Workers know about all the risks that may occur, but in the absence of sanctions from the company, workers do not adhere to the OSH culture. The workload in this company greatly affects the performance of its employees because they feel uncomfortable if they have to apply the OSH culture. Several workers are placed not according to their abilities. Meanwhile, the work environment at this location also greatly influences the performance of employees, because most of the workers are natives, so supervisors feel reluctant to reprimand workers if they do not apply the OSH culture. Conclusion: Based on the findings, workers are aware of the risks but feel uncomfortable applying the OSH culture. Therefore, it is recommended that the company implement stricter rules and issue warnings or sanctions for non-compliance. Additionally, conducting regular OSH training and safety talks can enhance employee adherence to the OSH culture.